Using Some Methods in Teaching Vocabulary in Russian - Sattarova Saodat Narzullayevna; Shokirova Shahrizoda Abdulaziz qizi (Zien Journals, 2021)
It is apparent that, there has been dramatically high interest and requirement for learning foreign languages in the last several decades in order to achieve personal and professional development. Because of this reason, modern pedagogy of 21st century faces a challenging task to teach a foreign language peculiar and more effective methods and approaches.
Keywords: RFL and UFL; effective methods; simulation; linguistic games; puzzles